THE CORRELATION BETWEEN VOCABULARY MASTERY AND SPEAKING SKILL - Roswita Rongga Milla; Dewa Ayu Ari Wiryadi Joni; Anak Agung Putu Arsana (Academic Journal on English Studies (AJOES), 2022)
The present study dealt with the correlation between vocabulary mastery and speaking skill of the eighth-grade students of SMP Pancasila Canggu in academic year 2021/2022. The samples were chosen by random sampling method with lottery system as many 38 students. The researchers used two tests to get the data vocabulary mastery and speaking skill, such as: fill in the blank items for the vocabulary mastery and video tell their experience for the speaking skill. The obtained data were analyzed by using Pearson Product Moment using SPSS 25.0 version windows. Based on the data analysis it showed that there is a high and significant correlation between vocabulary mastery and speaking skill of the eighth-grade students at SMP Pancasila Canggu in academic year 2021/2022. Therefore, it answered the research question that there is a significant correlation between vocabulary mastery and speaking skill.